2014
DOI: 10.1590/s1517-83822014000100006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficiency between two sampling plans for aflatoxins analysis in maize

Abstract: Variance and performance of two sampling plans for aflatoxins quantification in maize were evaluated. Eight lots of maize were sampled using two plans: manual, using sampling spear for kernels; and automatic, using a continuous flow to collect milled maize. Total variance and sampling, preparation, and analysis variance were determined and compared between plans through multifactor analysis of variance. Four theoretical distribution models were used to compare aflatoxins quantification distributions in eight m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…Probabilities associated with the two-tailed Student's t-test (p-value) for the dilution of the working samples (4, 8, 12 and 16%) homogenized in the devices Boerner, 16:1 multichannel splitter and 4:1 multichannel splitter to protect the quality at all stages: reception, storage and expedition. Mallmann et al (2014), studying manual and automatic sampling in the preparation of samples for aflatoxin analysis, concluded that the sampling operation contributed with the highest variability, followed by the stages of sample preparation and analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probabilities associated with the two-tailed Student's t-test (p-value) for the dilution of the working samples (4, 8, 12 and 16%) homogenized in the devices Boerner, 16:1 multichannel splitter and 4:1 multichannel splitter to protect the quality at all stages: reception, storage and expedition. Mallmann et al (2014), studying manual and automatic sampling in the preparation of samples for aflatoxin analysis, concluded that the sampling operation contributed with the highest variability, followed by the stages of sample preparation and analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Classification of grains is based on the comparison of the sample with a regulatory limit, a standard (Whitaker, 2006), which may be official or specific. Sampling efficiency is associated with the variation of the results generated and with the procedures adopted (Mallmann et al, 2013(Mallmann et al, , 2014, which involve sample collection, equipment for homogenization and preparation of the working sample (Whitaker et al, 2011). The phase of homogenization is fundamental and should be conducted with equipment that ensure representativeness of the initial lot.…”
Section: Introductionmentioning
confidence: 99%
“…Non-uniformity of the contamination within a grain mass leads to high variability in aflatoxin assessments and results that often conflict with expected norms (Mallmann et al., 2014). The maize used in this study was ideal for addressing the efficacy of hermetic storage.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling directly and only from a "hot zone" will unchain legal events that usually ends in the elimination of a whole feed batch, which is costly for feed manufacturers or importers/exporters [43]. On the other hand, research has demonstrated that the bulk of the variability in mycotoxin analysis comes from sampling [44]. Some papers have focused specifically on aflatoxin sampling.…”
Section: Feed Samplingmentioning
confidence: 99%